A Modified Strain‐Wedge Model for Small Strain Rigid Piles in Sand - Yisheng Yin; Dongyuan Wang; Kai Cui (Engineering Reports)
ABSTRACT This paper develops a modified strain‐wedge (MSW) model that accounts for the resistance to bending moments caused by the lateral frictional resistance and axial forces of piles in the small‐strain regime in sands and algorithmizes a finite differential analysis program. Two cases of rigid pile tests, one in Blessington and another in Shenton Park were used to calibrate the finite element analysis model and verify the proposed modified model. The results show that the analysis of pile‐side resistance is pivotal for rigid horizontally loaded monopiles, and the MSW model is the most accurate at predicting lateral displacement and the moments. Its accuracy in a small‐strain regime to predict the pile rotation points and the maximum bending moment is almost three times that of other models. With the increase of the soil strain, the accuracy of the MSW decreases. On the contrary, the prediction accuracy of numerical analysis using the UBC3D‐PLM constitutive model increases.